The Wreck of the Warship Northumberland on the Goodwin Sands, England, 1703: an interim report. (14th October 2014) - Pascoe, Daniel; Peacock, Robert
Abstract : The Northumberland, a third‐rate man‐of‐war was lost with all hands during the Great Storm of 26–27 November 1703 on the Goodwin Sands—famously known as 'the ship swallower'. It was rediscovered in 1980 by local divers following the location of a sister ship, the Stirling Castle . Since, the primary concern has been to record exposed structural remains, ordnance and artefacts, and interpret the wreck formation of the site. This paper describes the results of this work, and discusses in particular the size of the keel, the use of chocks, and standardization of ordnance in the Restoration Navy through reference to comparable ship‐finds and historical records.